Free fatty acid receptor 4 (FFA4) activation ameliorates 2,4-dinitrochlorobenzene-induced atopic dermatitis by increasing regulatory T cells in mice - Son So-Eun; Park Soo-Jin; Koh Jung-Min; Im Dong-Soon (Acta Pharmacologica Sinica, 2020)
High dose intake of docosahexaenoic acid showed beneficial effects on atopic dermatitis in patients and was found to increase regulatory T cells in mice, but its molecular target has not been identified. Free fatty acid receptor 4 (FFA4, also known as GPR120) is a receptor sensing polyunsaturated long-chain fatty acids including docosahexaenoic acid. In the present study, we examined whether FFA4 acted as a therapeutic target of docosahexaenoic acid for treating atopic dermatitis. Experimental atopic dermatitis was induced in mice by 2,4-dinitrochlorobenzene (DNCB) sensitization on day 0, followed by repeated DNCB challenges from D7 to D48. The mice were treated with a selective agonist compound A (30 mg· kg−1· d−1, ip) from D19 to D48, and sacrificed on D49. We found that DNCB-induced atopic dermatitis-like skin lesions, i.e. hypertrophy and mast cell infiltration in skin tissues, as well as markedly elevated serum IgE levels. Administration of compound A significantly suppressed the atopic responses in ears and lymph nodes, such as hypertrophy and mast cell infiltration in the ears, enlarged sizes of lymph nodes, and elevated serum IgE and levels of cytokines IL-4, IL-13, IL-17, and IFN-γ in ear tissue. The therapeutic effects of compound A were abolished by FFA4 knockout. Similarly, increased CD4+Foxp3+ regulatory T-cell population in lymph nodes was observed in wide-type mice treated with compound A, but not seen in FFA4-deficient mice. In conclusion, we demonstrate that activation of FFA4 ameliorates atopic dermatitis by increasing CD4+Foxp3+ regulatory T cells, suggesting FFA4 as a therapeutic target for atopic dermatitis.